The impact of exercise intensity on the release of cardiac biomarkers in marathon runners - Legaz Arrese, Alejandro; George, Keith; Carranza García, Luis Enrique; Munguía Izquierdo, Diego; Moros García, Teresa; Serrano Ostáriz, Enrique (Springer, 2011)
We sought to determine the influence of exercise intensity on the release of cardiac troponin I (cTnI) and N-terminal pro-brain natriuretic peptide (NT-proBNP) in amateur marathon runners. Fourteen runners completed three exercise trials of the same duration but at exercise intensities corresponding to: (a) a competitive marathon [mean ± SD: heart rate 159 ± 7 beat min-1 , finish time 202 ± 14 min]; (b) 95% of individual anaerobic threshold [heart rate 144 ± 6 beat min-1 ] and; (c) 85% of individual anaerobic threshold [heart rate 129 ± 5 beat min-1 ]. cTnI and NT-proBNP were assayed from blood samples collected before, 30 min and 3 h post-exercise for each trial. cTnI and NT-proBNP were not different at baseline before each trial. After exercise at 85% of individual anaerobic threshold cTnI was not significantly elevated. Conversely, cTnI was elevated after exercise at 95% of individual anaerobic threshold (0.016 lg L-1) and to an even greater extent after exercise at competition intensity (0.054 lg L-1 ). Peak post-exercise values of NT-proBNP were elevated to a similar extent after all exercise trials (P\0.05). The upper reference limit for cTnI (0.04 lg L-1 ) was exceeded in six subjects at competition intensity. No data for NT-proBNP surpassed its upper reference limit. Peak post-exercise values for cTnI and NTproBNP were correlated with their respective baseline values. These data suggest exercise intensity influences the release of cTnI, but not NT-proBNP, and that competitive marathon running intensity is required for cTnI to be elevated over its upper reference limit